The Effect of General Anesthesia compared to Spinal Anesthesia for Caesarean Section on Neonatal APGAR Score - christiana, monica; Bisri, Tatang (Majalah Anestesia dan Critical Care, 2015)
For the last decades, Casearean delivery cases has increased significantly. The choice of anesthesia technique for surgical procedure consider its safety for both the mother and neonates. Neonatal APGAR scoring has been used as the parameter of neonate’s well being and success of obstetric anesthesia technique. Several previous studies have recommended the excellence of regional anesthesia compared to general one. This study was conducted to compare the effect of general anesthesia to spinal anesthesia on the APGAR score of the neonates. The objective of this study is to describe the general anesthesia and spinal anesthesia effect in Caesarean delivery on AGPAR score. Rertospective study of 64 parturient patients underwent elective Caesarean section from January to June 2015. Data were obtained from medical record of Melinda Mother and Child Hospital, Bandung. Subjects were distributed into 2 groups of 32 patients each. Group I underwent general anesthesia, while the other underwent spinal anesthesia. Parameter asessments were APGAR, blood pressure, pulse, and okxygen saturation. Data recoded were analized with t test and p<0.05 considered as significant. First minute APGAR scores were recorded unsignificantly higher (p=0.326) in Group I (8.87± 0.33) compared to Group II (8.78± 0.42). However, fifth minute APGAR scores were significantly (p=0.000) better in Group II (9.75±0.46) compared to Group I (9.25±0.44). Spinal anesthesia technique in caesarean section procedure had a significantly better effect on neonatal APGAR score compared to genaral anesthesia.